Pancasila Village, Multicultural Education and Moderation of Diversity in Indonesia - Khoirul Anwar (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This paper is a study field of multicultural education as an effort of moderation of diversity in Indonesia, by including Sukoreno village of Jember which is a miniature of diversity on Indonesian diversity as the village of Pancasila. This theme is a new issue in the world of education in Indonesia, but this thema is the subject that is particularly important due to the diversity that exists in Indonesia has the potential for great conflict. This research uses qualitative research with a case study approach, and analyze with relevant theories and the results of previous studies. The result of this study First Sukoreno called as Pancasila village. The name of Pancasila village derived from diverse religions such as Islam, Hindu, Buddhist and Christian, Catholic, and all of it was built with a high sense of tolerance and harmonization. Second The education in Sukoreno village does not look at the religious differences they have. One institution has teacher and student with difference beliefs and do not create problems and conflicts occur. Third A very high tolerance in Sukoreno society creates a sense of peace, harmony, mutual respect among each other as the original form of the actual ideology of Pancasila